2021
DOI: 10.1215/00703370-8996307
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Persons in China Living More Years in an Independent Living Arrangement? Estimates Using Multistate Life Tables

Abstract: Adopting a multistate life table approach, this study estimates number of years the very old in China expect to live in an independent living arrangement (alone or with spouse only)—an estimate we term “independent living life expectancy” (ILLE)—as opposed to in coresidence with adult children or others. We also estimate how ILLE and proportion of total life expectancy (TLE) residing independently has changed over time. The backdrop for this study is a society experiencing both increasing longevity and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…The rest types of living arrangements were uncommon. The results were consistent with previous findings that co-residing with one or more adult children is still a fundamental household structure in China ( 15 ). Living arrangement patterns were also found to be significantly correlated with the oldest-old health lifestyles.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rest types of living arrangements were uncommon. The results were consistent with previous findings that co-residing with one or more adult children is still a fundamental household structure in China ( 15 ). Living arrangement patterns were also found to be significantly correlated with the oldest-old health lifestyles.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Even with dramatic changes in Chinese society, traditional family norms have remained. An older adult co-residing with one or more adult children has still been a long-standing and continuing practice and a fundamental way of household structure in China ( 15 ). Living with sons has still been prevalent, even if living with daughters has become more desirable and more common ( 16 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on sample studies, such a percentage increased from about 18.0% in 2002 to more than 25.0% in 2018 [44]. 3) Older adults living in a multigenerational family has been less common in recent years [44][45][46][47]. In year 2016, the percentage of Hong Kong elders living with adult children became lower than 50.0% [48].…”
Section: Changing Patterns Of Living Arrangements Among Older Adultsmentioning
confidence: 99%
“…The positive or negative association between older adults' health and living with adult children or co-residing in a multigenerational family has been found to be strengthened over time [23,45,54,55]. As to the negative effects of living with adult children, it was found that Chinese older adults who changed their status from not living with adult children to living with children had significantly higher frailty indices with time [56].…”
Section: Dynamic Relationship Between Living Arrangements and Older A...mentioning
confidence: 99%